Descriptive Results Of Digital Dentisty Readiness Among Dental Practitioners In Malaysia - Rahmayanti Laya, Sitti Andi; Sarkawi, Farida; Mohd Noor, Siti Noor Fazliah (2010)
Technology application in dentistry evolved dramatically allowing easy data management. Dental practice equipped by ICT application enables the improvement in work flow and efficiency due to huge number of software available that serves many non-internet clinical applications as well as administrative application technology.